Overcoming Alcohol Problems, Workbook : a Cognitive-Behavioral Treatment Program. - Epstein, Elizabeth E. (Treatments that work., 2009)
Alcohol use can have negative effects on your day-to-day functioning, health, and relationships. If drinking is a problem in your life, this program can help you regain control. It has been developed with the benefit of each author's 25+ years of clinical experience in treating substance abusers and has been proven effective in helping individuals to achieve and maintain abstinence. Over the course of 12 weeks, you will meet with a qualified mental health or addictions professional to learn various skills and strategies for quitting drinking and staying sober. Together, you will come up with a.